Indirect boundary element formulation with dual reciprocity in elastodynamics. (November 2022) - Naga, Taha H.A.; Elsheikh, Elsayed M.; Rashed, Youssef F.
Abstract: In this paper, a new indirect boundary element formulation for two-dimensional elastodynamic problems is presented. The formulation makes use of a static fundamental solution. For accurate solution, the location of the fictitious boundary is chosen to be the same as problem boundary. The relevant fundamental solution is integrated over lines. The method is combined with the Dual Reciprocity Method (DRM), for handling the domain integral concerning to the domain inertia terms. A suitable approximation (traditional function C-R is used) for the inertia terms (or, domain accelerations), is used to transform the domain integral to the boundary. The discretization is performed on the boundary, or a boundary-like geometry. The method is easy to code and efficient as presented by the numerical examples.